PRINCIPLE OF PROCEDURAL ECONOMY IN THE CIVIL PROCESS OF UKRAINE AND FOREIGN COUNTRIES: COMPARATIVE LEGAL CHARACTERISTICS - Iryna V. Pasailiuk (Alfred Nobel University Journal of Law, 2024)
The article is devoted to study the principle of procedural economy in the civil process of Ukraine. It is focused on the foreign experience of the leading countries of the world and the implementation of civil law in national legislation. The specification of the principle of procedural economy of civil law and its consoli- dation in the current legislation are dictated by the actual circumstances that exist in law enforcement ac- tivities and are conditioned by trends in the development of procedural branches of law, as well as the im- plementation of procedural rights and obligations, in particular, the obstruction of violation of reasonable terms of proceedings, the cessation of delaying the trial, and the improvement of the efficiency of justice. It is specified that courts of general jurisdiction in their decisions increasingly recognize procedural econo- my as a principle and refer to it when considering cases. The principle of procedural economy is aimed pri- marily at speeding up the consideration of the case (dispute resolution) and reducing legal costs. The prin- ciple of procedural economy (efficiency, reasonableness and rationality of the judicial process), in the as- pect of a person’s right to appeal a court decision, provides for the possibility of restricting such a right in relation to certain types of «intermediate» defined by law (procedural) court decisions, provided that the disagreement of one of the parties with such an «interim» court decision can be expressed in the relevant appeal or cassation appeal against the «main» court decision («final» decision on the merits of the case) in accordance with the guarantees enshrined, separate, in Article 129 of the Constitution of Ukraine (a per- son’s right to appeal (second) review of the case). The absence of a literal consolidation of the principle of procedural economy in the norms of domestic civil procedural law creates certain difficulties, since it vio- lates one of the axioms of law, in particular the principle of legal certainty. It is concluded that the applica- tion of the principle of procedural economy by the courts allows us to consider the case as a whole in a rea- sonable time, prevents the parties from abusing their procedural rights, and also guarantees a careful atti- tude to the resources of all participants in the case. Legislative consolidation of the principle of procedural economy will help to create in the future a solid foundation for stopping the abuse of procedural rights and the ability to determine the vector of many procedural actions by specifying a number of civil law norms that ensure the cessation of such behavior.